2022
DOI: 10.3340/jkns.2021.0167
|View full text |Cite
|
Sign up to set email alerts
|

Value of Additional Instrumented Fusion in the Treatment of Thoracic Ossification of the Ligamentum Flavum

Abstract: Objective :The ossification of the ligamentum flavum (OLF) is one of the major causes of thoracic myelopathy. Surgical decompression with or without instrumented fusion is the mainstay of treatment. However, few studies have reported on the added effect of instrumented fusion. The objective of this study was to compare clinical and radiological outcomes between surgical decompression without instrumented fusion (D-group) and that with instrumented fusion (F-group). Methods : A retrospective review was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Surgical decompression is required when myelopathy progresses, and the effectiveness of decompression surgery for OLF has been demonstrated in previous studies 8) . Various studies have reported sufficient treatment effects with only decompression surgery, and recurrence is uncommon 6,8,15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical decompression is required when myelopathy progresses, and the effectiveness of decompression surgery for OLF has been demonstrated in previous studies 8) . Various studies have reported sufficient treatment effects with only decompression surgery, and recurrence is uncommon 6,8,15) .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a combined fixation technique has been used; however, given the pathophysiology potentially triggered by micro-movements or macro-movements, especially associated with partial facet removal during decompression, it may be reasonable to stabilize the motion via screw fixation after decompression 1,5,6,13,18,20) . Hwang et al 6) reported that screw fixation is beneficial for the progression of kyphosis in OLF. However, the need for fixation for specific patients is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It may be worth considering whether decompression surgery alone, without instrumented fusion, is sufficient for OLF in the thoracolumbar junction, while there have been some positive reports regarding the effectiveness of decompressive instrumented fusion for thoracic OLF [7,8]. The available evidence is insufficient for making clear judgments.…”
Section: Ct: Computed Tomographymentioning
confidence: 99%